METHOD OF AIRCRAFT LANDING BY CURVILINEAR GLIDE PATHS WITHIN THE BOUNDARY TRAJECTORIES - Pavlova, Svitlana; Voloshenyuk, Dmytro (Proceedings of National Aviation University (archive), 2017)
Purpose: The paper is dedicated to improving of civil aviation flight safety question by the way of new method of aircraft landing by curvilinear glide paths within the boundary trajectories. Proposed method ordered for improving of safety level, sustainability and cost effectiveness of the aircraft landing with own individual, optimal vertical descending profile from flight level to the runway threshold. Methods: Landing method, based on generation (calculation and construction) of virtual curvilinear glide paths of landing within the boundary trajectories with taking into account of “fully controllable state areas” of aircraft has been proposed. Results: New aircraft landing method that has large profit in the reducing of the level of noises, fuel consumption and harmful emissions. Discussion: The essence of the method consists in using of fully controllable state areas that are constructed taking into account on linearity in aircraft flight characteristics, probable changes into environmental state, criterion of landing implementation optimality, all functional and aerodynamic aircraft capabilities for virtual curvilinear glide path construction, meant by some aircraft traffic trajectory for time and distance reducing, that are necessary for stage from start of descending from flight level to runway threshold.